Survey of per- and polyfluoroalkyl substances (PFAS) in surface water collected in Pensacola, FL. Issue 8 (August 2022) - da Silva, Bianca Ferreira; Aristizabal-Henao, Juan J.; Aufmuth, Joe; Awkerman, Jill; Bowden, John A.
Abstract: As the persistence of per- and polyfluoroalkyl substances (PFAS) become a global concern, information about the occurrence and characteristics of PFAS in estuarine and marine ecosystems is poorly represented. In this study, the presence of 51 PFAS were monitored in the Pensacola Bay System (PBS), Florida, USA. Due to the presence of many potential PFAS sources in close proximity to the PBS (e.g., military bases, industries, airports and several firefighting stations), the distribution and concentration of PFAS in this estuarine environment provides insights into the fate of these complex compounds as well as the possible impacts on coastal systems. Surface water was collected and analyzed from 45 different sites via Strata-X-AW cartridge extractions and ultra-high pressure liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) analysis. Recoveries for many PFAS (13/51) were >60% (mean 77 %), with relative standard deviations below 20%, except for N-methylperfluoro-1-octanesulfonamidoacetic acid (N-MeFOSAA) (22%). Of the perfluoroalkyl carboxylic acids (PFCAs), which comprised the majority of PFAS detected: perfluorooctanoic acid (PFOA) and perfluorohexanoic acid (PFHxA) were present in all samples; however, perfluoropentanoic acid (PFPeA) was the individual PFAS with the highest concentration of this group (51.9 ng.L −1, at site 81). The PFAS detected at the highest concentrations were perfluoroalkyl sulfonic acids (PFSA), with perfluorooctane sulfonic acid (PFOS) having the highest detected concentration (269 ng.L −1, at site 81). At all sites, at least eight or more PFAS were quantified. Past and current use of PFAS-containing materials and their fate in areas surrounding military bases, airports, and industries, require more in-depth monitoring efforts to better determine the need for regulation, management, and/or remediation. Here, sites located close to areas suspected of PFAS use had elevated concentrations. For example, one coastal location near an airfield had a ΣPFAS of 677 ng.L −1 . Expansion from these ongoing efforts will focus on assessment of PFAS-related effects in local wildlife and evaluating the distribution of PFAS at these "hotspot" sites during large episodic weather events, a critically understudied phenomenon regarding PFAS and vulnerable coastal environments. Highlights: Elevated PFAS levels were quantified in Pensacola Bay surface water. ΣPFOS was the compound detected with the highest concentration between all PFAS. PFAS diversity increased near sites with industrial effluent and suspected AFFF usage. Abstract : PFAS, Surface water, Pensacola bay system, Coastal water monitoring, AFFF usage, UHPLC-MS/MS.